KPC-producing Klebsiella pneumoniae in Switzerland from 2024 to 2025: comparative genomics and cefiderocol resistance mechanisms analyses - Jacqueline Findlay; Patrice Nordmann; R Lienhard; L Vonallmen; C Schilt; A Scherler; K Lucke; M Jutzi; M Reichmuth; U Schibli; C Fricker; S Pranghofer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

In vitro activity of β-lactamase inhibitors avibactam, relebactam and vaborbactam in combination with aztreonam against metallo-β-lactamase producing Escherichia coli clinical isolates - Clément Viguier; Samanta Freire; Maxime Bouvier; Christophe Le Terrier; Laurent Poirel; A. Westers; M. Imperiali; L. Pozzi; D. Balzari; G. Vaninetti; C. Cirillo; V. Gaia; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Repeated identification of plant-associated polerovirus 3 (PaPV3) and of a novel polerovirus in the virome of French grain cereals - L. Svanella-Dumas; A. Marais; C. Faure; B. Bergey; R. Comte; T. Candresse (Archives of Virology, 2026)

Genetic Diversity Impacts Climate‐Induced Species Range Shifts - Brunno F. Oliveira; Romain Bertrand; Lise Comte; Jonathan Lenoir; Gaël Grenouillet; Lesley T. Lancaster; Jérôme Murienne; Sarah Diamond; Brett R. Scheffers; R. M. W. J. Bandara; Jake A. Lawlor; Nikki A. Moore; et al. (Ecology Letters, 2026)
Climate change threatens biodiversity when species cannot tolerate, adapt to, or track shifting environmental conditions to stay within their climatic niches. A major unresolved question is whether and how species' genetic diversity modulates these dynamics, buffering against range contractions or facilitating range expansions. To test this, we integrated the largest global databases of species range shifts and genetic diversity, encompassing 4673 range shift estimates for 1888 species with available genetic data, including insects, arachnids, birds, fish, and plants. We found that range shifting rates were significantly shaped by the interaction of genetic diversity and climate change velocity. Under rapid warming, species with higher genetic diversity exhibited reduced trailing edge contractions, likely reflecting enhanced evolutionary potential or reduced vulnerability to drift. Under moderate warming, species with higher genetic diversity shifted more rapidly at leading edges and range centroids, consistent with greater colonisation ability. Our study provides evidence that genetic diversity potentially enables persistence at the trailing edge and colonisation at the leading edge, with the magnitude of these effects varying depending on the velocity of climate change.

Characterization of French isolates of wheat mosaic virus and identification of multiple variants of genomic RNAs 5 and 6 - T. Candresse; L. Svanella-Dumas; Aijun Huang; C. Faure; R. Comte; A. Marais (Archives of Virology, 2026)

Combined resistance mechanisms leading to high-level of cefiderocol resistance among NDM-like producing E. coli ST167 clinical isolates - Mustafa Sadek; Juan Bosch Duran; Trinad Chakraborty; Laurent Poirel; R. Lienhard; L. Vonallmen; C. Schilt; A. Scherler; K. Lucke; M. Jutzi; M. Reichmuth; V. Slutter; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Summary Purpose A series of NDM-producing Escherichia coli ST167 clinical isolates exhibiting resistance to cefiderocol (FDC), with no previous exposure to this antibiotic, were analyzed in this study. Methods The antimicrobial susceptibility testing and phenotypic detection of resistance patterns (Rapid Cefiderocol NP test and MIC determination) were performed for all tested isolates. Their entire genomes were sequenced by using the Illumina MiSeq platform and high-quality reads were de-novo assembled using the CLC Genomic Workbench. Genome-sequence based characteristics were analyzed using bioinformatics tools. Results All NDM-producing E. coli ST167 isolates showed a high level of resistance to FDC (MICs being 64 or > 64 mg/L). The chromosomally located cirA gene, encoding a catecholate siderophore receptor in E. coli , was truncated in all FDC-resistant isolates due to a frameshift mutation (S90Y), leading to CirA-deficient isolates. A four amino acid insertion (YRIN) was also identified after residue 333 in the PBP3 protein sequence of all E. coli isolates. Among them, a single FDC-resistant NDM-5-producing E. coli isolate (1006) was additionally resistant to aztreonam/avibactam (AZA MIC of 8 mg/L). When analyzed against the genome of another FDC resistant NDM-5 producing E. coli ST167 containing a YRIN insertion in the PBP3, and exhibiting decreased susceptibility to AZA, the broad-spectrum ß-lactamase CMY-42 was identified. Conclusion We identified a variety of NDM-producing E. coli isolates exhibiting high level of resistance to FDC as a result of the combined effect of CirA deficiency, along with production of NDM-type enzymes. The spread of such resistance phenotype across Europe poses great concern on the clinical efficacy of this novel drug. Additionally, the identification of an FDC- and AZA-resistant NDM-5 producing E. coli isolate represents one of the ultimate evolutions with a possible step towards pan-resistance.

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Nanoparticle Counting for PTI: The Dirty Tail Paradigm — A Pragmatic Proposal to Strongly Reduce Urban PN Pollution from Combustion Engine Fleets - A. Mayer; J. Czerwinski; Th. Lutz; F. Legerer; M. Wyser; P. Comte; L. Larsen; L. Rubino; K. Vasilatou; D. Engelmann; M. Knoll; H. Burtscher (Emission Control Science and Technology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Bringing traits back into the equation: A roadmap to understand species redistribution - Lise Comte; Romain Bertrand; Sarah Diamond; Lesley T. Lancaster; Malin L. Pinsky; Brett R. Scheffers; J. Alex Baecher; R. M. W. J. Bandara; I‐Ching Chen; Jake A. Lawlor; Nikki A. Moore; Brunno F. Oliveira; et al. (Global Change Biology, 2024)
Ecological and evolutionary theories have proposed that species traits should be important in mediating species responses to contemporary climate change; yet, empirical evidence has so far provided mixed evidence for the role of behavioral, life history, or ecological characteristics in facilitating or hindering species range shifts. As such, the utility of trait‐based approaches to predict species redistribution under climate change has been called into question. We develop the perspective, supported by evidence, that trait variation, if used carefully can have high potential utility, but that past analyses have in many cases failed to identify an explanatory value for traits by not fully embracing the complexity of species range shifts. First, we discuss the relevant theory linking species traits to range shift processes at the leading (expansion) and trailing (contraction) edges of species distributions and highlight the need to clarify the mechanistic basis of trait‐based approaches. Second, we provide a brief overview of range shift–trait studies and identify new opportunities for trait integration that consider range‐specific processes and intraspecific variability. Third, we explore the circumstances under which environmental and biotic context dependencies are likely to affect our ability to identify the contribution of species traits to range shift processes. Finally, we propose that revealing the role of traits in shaping species redistribution may likely require accounting for methodological variation arising from the range shift estimation process as well as addressing existing functional, geographical, and phylogenetic biases. We provide a series of considerations for more effectively integrating traits as well as extrinsic and methodological factors into species redistribution research. Together, these analytical approaches promise stronger mechanistic and predictive understanding that can help society mitigate and adapt to the effects of climate change on biodiversity.

Molecular analysis of metallo-beta-lactamase-producing Pseudomonas aeruginosa in Switzerland 2022–2023 - Jacqueline Findlay; Otavio Hallal Ferreira Raro; Laurent Poirel; Patrice Nordmann; R. Lienhard; L. Vonallmen; C. Schilt; A. Scherler; K. Lucke; M. Jutzi; M. Reichmuth; U. Schibli; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Objectives The occurrence of metallo-beta-lactamase-producing Pseudomonas aeruginosa (MBL-PA) isolates is increasing globally, including in Switzerland. The aim of this study was to characterise, phenotypically and genotypically, the MBL-PA isolates submitted to the Swiss National Reference Center for Emerging Antibiotic Resistance (NARA) reference laboratory over a 12-month period from July 2022 to July 2023. Methods Thirty-nine non-duplicate MBL-PA Isolates were submitted to NARA over the study period from across Switzerland. Susceptibility was determined by broth microdilution according to EUCAST methodology. Whole-genome sequencing was performed on 34 isolates. Sequence types (STs) and resistance genes were ascertained using the Centre for Genomic Epidemiology platform. MBL genes, bla NDM-1 , bla IMP-1 , and bla VIM-2 , were cloned into vector pUCP24 and transformed into P. aeruginosa PA14. Results The most prevalent MBL types identified in this study were VIM (21/39; 53.8%) followed by NDM (11/39; 28.2%), IMP (6/39; 15.4%), and a single isolate produced both VIM and NDM enzymes. WGS identified 13 different STs types among the 39 isolates. They all exhibited resistance to cephalosporins, carbapenems, and the beta-lactam-beta-lactamase inhibitor combinations, ceftolozane-tazobactam, ceftazidime-avibactam, imipenem-relebactam, and meropenem-vaborbactam, and 8 isolates were cefiderocol (FDC) resistant. Recombinant P. aeruginosa strains producing bla NDM-1 , bla IMP-1 , and bla VIM-2 exhibited FDC MICs of 16, 8, and 1 mg/L, respectively. Conclusions This study showed that the MBL-PA in Switzerland could be attributed to the wide dissemination of high-risk clones that accounted for most isolates in this study. Although FDC resistance was only found in 8 isolates, MBL carriage was shown to be a major contributor to this phenotype.

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

RivFishTIME: A global database of fish time‐series to study global change ecology in riverine systems - Lise Comte; Juan Carvajal‐Quintero; Pablo A. Tedesco; Xingli Giam; Ulrich Brose; Tibor Erős; Ana F. Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Sapna Sharma; et al. (Global Ecology and Biogeography, 2021)
Motivation We compiled a global database of long‐term riverine fish surveys from 46 regional and national monitoring programmes and from individual academic research efforts, with which numerous basic and applied questions in ecology and global change research can be explored. Such spatially and temporally extensive datasets have been lacking for freshwater systems in comparison to terrestrial ones. Main types of variables contained The database includes 11,386 time‐series of riverine fish community catch data, including 646,270 species‐specific abundance records, together with metadata related to the geographical location and sampling methodology of each time‐series. Spatial location and grain The database contains 11,072 unique sampling locations (stream reach), spanning 19 countries, five biogeographical realms and 402 hydrographical basins world‐wide. Time period and grain The database encompasses the period 1951–2019. Each time‐series is composed of a minimum of two yearly surveys (mean = 8 years) and represents a minimum time span of 10 years (mean = 19 years). Major taxa and level of measurement The database includes 944 species of ray‐finned fishes (Class Actinopterygii). Software format csv. Main conclusion Our collective effort provides the most comprehensive long‐term community database of riverine fishes to date. This unique database should interest ecologists who seek to understand the impacts of human activities on riverine fish biodiversity and to model and predict how fish communities will respond to future environmental change. Together, we hope it will promote advances in macroecological research in the freshwater realm.

Interactions of diffuse and focused allogenic recharge in an eogenetic karst aquifer (Florida, USA) - Abigail L. Langston; Elizabeth J. Screaton; Jonathan B. Martin; Vincent Bailly-Comte (Hydrogeology Journal, 2012)

Amplitude and frequency characteristics of the 2001 Southern Peru, M w = 8.4 earthquake records - Rubén L. Boroschek; Diana Y. Comte (Journal of Seismology, 2006)